Platelet releasate promotes skeletal myogenesis by increasing muscle stem cell commitment to differentiation and accelerates muscle regeneration following acute injury. (14th November 2018) - Scully, David; Sfyri, Peggy; Verpoorten, Sandrine; Papadopoulos, Petros; Muñoz‐Turrillas, María Carmen; Mitchell, Robert; Aburima, Ahmed; Patel, Ketan; Gutiérrez, Laura; Naseem, Khalid M.; Matsakas, Antonios
Abstract: Aim: The use of platelets as biomaterials has gained intense research interest. However, the mechanisms regarding platelet‐mediated skeletal myogenesis remain to be established. The aim of this study was to determine the role of platelet releasate in skeletal myogenesis and muscle stem cell fate in vitro and ex vivo respectively. Methods: We analysed the effect of platelet releasate on proliferation and differentiation of C2C12 myoblasts by means of cell proliferation assays, immunohistochemistry, gene expression and cell bioenergetics. We expanded in vitro findings on single muscle fibres by determining the effect of platelet releasate on murine skeletal muscle stem cells using protein expression profiles for key myogenic regulatory factors. Results: TRAP6 and collagen used for releasate preparation had a more pronounced effect on myoblast proliferation vs thrombin and sonicated platelets ( P < 0.05). In addition, platelet concentration positively correlated with myoblast proliferation. Platelet releasate increased myoblast and muscle stem cell proliferation in a dose‐dependent manner, which was mitigated by VEGFR and PDGFR inhibition. Inhibition of VEGFR and PDGFR ablated MyoD expression on proliferating muscle stem cells, compromising their commitment to differentiation in muscle fibres ( P < 0.001). Platelet releasate was detrimental to myoblast fusion and affected differentiation of myoblasts in a temporal manner. Most importantly, we show that platelet releasate promotes skeletal myogenesis through the PDGF/VEGF‐Cyclin D1‐MyoD‐Scrib‐Myogenin axis and accelerates skeletal muscle regeneration after acute injury. Conclusion: This study provides novel mechanistic insights on the role of platelet releasate in skeletal myogenesis and set the physiological basis for exploiting platelets as biomaterials in regenerative medicine.